Recent Syntheses and Biological Activity of Lentiginosine and its Analogues - M. Cordero, Franca; Giomi, Donatella; Brandi, Alberto (Current Topics in Medicinal Chemistry, 2014)
(+)-Lentiginosine, a natural trans-1,2-dihydroxyindolizidine belonging to the class of iminosugars, is a potent inhibitor of amyloglucosidase, and a good inhibitor of Hsp90. The non-natural enantiomer, (–)-lentiginosine, induces apoptosis on tumor cells of different origin and is poorly cytotoxic towards non-transformed cells. The significant biological activity of these compounds has resulted in the development of many synthetic approaches for their preparation. This review is an update of a previous survey and summarizes the most recent achievements on biological studies as well as total syntheses of lentiginosine and trans-1,2-dihydroxyindolizidine analogues.
Keywords: Alkaloids